2021
DOI: 10.3390/antiox10060909
|View full text |Cite
|
Sign up to set email alerts
|

Transit and Metabolic Pathways of Quercetin in Tubular Cells: Involvement of Its Antioxidant Properties in the Kidney

Abstract: Quercetin is a flavonoid with antioxidant, antiviral, antimicrobial, and anti-inflammatory properties. Therefore, it has been postulated as a molecule with great therapeutic potential. The renoprotective capacity of quercetin against various toxins that produce oxidative stress, in both in vivo and in vitro models, has been shown. However, it is not clear whether quercetin itself or any of its metabolites are responsible for the protective effects on the kidney. Although the pharmacokinetics of quercetin have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…After i.p. administration, metabolism in enterocytes does not take place [12], while a first-pass effect occurs via p.o., with the compound being biotransformed before entering systemic circulation [26]. Therefore, the nephroprotection of quercetin against cisplatin could be related to the concentrations reached in the kidney by quercetin itself or its metabolites, which could be different depending on the administration route of the flavonoid.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…After i.p. administration, metabolism in enterocytes does not take place [12], while a first-pass effect occurs via p.o., with the compound being biotransformed before entering systemic circulation [26]. Therefore, the nephroprotection of quercetin against cisplatin could be related to the concentrations reached in the kidney by quercetin itself or its metabolites, which could be different depending on the administration route of the flavonoid.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be speculated that the use of quercetin 3'-O-glucuronide might still improve the cytoprotective effect observed for quercetin 3-O-glucuronide in the present work. It has also been suggested that these metabolites could be involved in the induction of antioxidant defense mechanisms through inducing the expression of antioxidant enzymes [12]. In addition, some published studies have demonstrated therapeutic effects of glucuronide metabolites [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations